Autonomy-Based STEM Learning: An Innovative Solution to Improve Students’ Digital Literacy - Suyidno, Suyidno; Maisarah, Siti; Miriam, Sarah; Mahtari, Saiyidah (FKIP Universitas Lampung, 2022)
In the current era of technology and information, digital literacy is a critical factor for life and career success, but it has received less attention in schools. Therefore, this study aims to analyze the effectiveness of Autonomy-Based STEM learning (A-STEM learning) in improving students' digital literacy. This research uses the ADDIE development model. The implementation test used a one-group pre-test post-test design on 29 students in class XI MIPA in one of the high schools in Banjarmasin, South Kalimantan, Indonesia. Data collection used a digital literacy questionnaire that emphasized indicators of the intensity of application and utilization of digital literacy in learning activities; the number and variety of teaching materials and digital-based teaching aids; the frequency of accessing digital teaching materials; having operational skills in using ICT for learning and learning outcomes tests. The results obtained the n-gain value of digital literacy and learning outcomes of 0.74 and 0.85, respectively, with a high criteria. Thus, the developed A-STEM learning effectively improves students' digital literacy in physics. Keywords: Autonomy-based STEM learning, digital literacy, learning outcomes. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1069-1081